2014
DOI: 10.3389/fmed.2014.00030
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bacteria Bearing Resistant Biofilm Forms, by Using the Universal and Specific PCR is Still Unhelpful in the Diagnosis of Periprosthetic Joint Infections

Abstract: Intraoperative conventional bacteriological cultures were compared with different polymerase chain reaction (PCR) methods in patients with total joint arthroplasties. The isolated bacteria were investigated for biofilm formation, and the biofilm forming strains, in their planktonic and biofilm forms, were further tested for their antimicrobial resistance against several clinically important antimicrobials. Forty four bone and joint samples were included and classified as infected or non-infected according to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Most studies, albeit heterogeneous in their methodology, have yielded variable results, and overall, molecular diagnostics have not been shown to be consistently better than culture, the current gold standard (38). Our study has shown that synovial fluid PCR has lower sensitivity than culture; however, it did detect two S. aureus PJI cases that were negative by synovial fluid culture.…”
Section: Discussionmentioning
confidence: 53%
“…Most studies, albeit heterogeneous in their methodology, have yielded variable results, and overall, molecular diagnostics have not been shown to be consistently better than culture, the current gold standard (38). Our study has shown that synovial fluid PCR has lower sensitivity than culture; however, it did detect two S. aureus PJI cases that were negative by synovial fluid culture.…”
Section: Discussionmentioning
confidence: 53%
“…The protective effect of the higher dose (2 g) of cefazolin may be more beneficial than that of the lower dose (1 g) due to the longer persistence of the inhibitory effect, particularly in the final period of the operation. A previous study found that biofilm formation could develop for up to 1–2 days [ 12 ]; therefore, hypothetically, the higher dose (2 g) of cefazolin might be more beneficial than the lower dose of 1 g. Second, the recommendations for surgeons from the results of the present study might appear to be weak because of the lack of evidence concerning relationships between the intraosseous concentration of cefazolin, its inhibitory effect and the related infection. This issue relates to the previous limitation mentioned, as there was no clarification of those relationships during the final period of the operation.…”
Section: Discussionmentioning
confidence: 67%
“…Both methods detected 16s rRNA. 32 They found that the specific PCR had better results than universal, but both had issues when compared to culture. They state that PCR may not replace the gold standard of cultural because of its interpretative problems and that perhaps could be used if small amount of sample were available or when there was a negative culture after 24h of incubation.…”
Section: Pcr Usage In Synovial Fluidmentioning
confidence: 99%
“…They state that PCR may not replace the gold standard of cultural because of its interpretative problems and that perhaps could be used if small amount of sample were available or when there was a negative culture after 24h of incubation. 32 The issue with broad range PCR is that while it has a high specificity, there is often a poor sensitivity in diagnosing infections. 33 However when the PCR and bacterial cultural were considered together, the sensitivity of PCR increased to 67%.…”
Section: Pcr Usage In Synovial Fluidmentioning
confidence: 99%